Cowboys & aliens - Favreau, Jon.; Grazer, Brian, 1953-; Orci, Roberto; Craig, Daniel; 1968-; Ford, Harrison, 1942- (Universal City, CA : Universal Studios Home Entertainment, 2011)
In Arizona in 1873, a stranger leads a posse of cowboys, outlaws and Apache warriors against an alien enemy.
Originally released as a motion picture in 2011./ "Based on Platinum 'Studios' Cowboys and aliens by Scott Michael Rosenberg."/ Participants: Daniel Craig, Harrison Ford, Olivia Wilde, Sam Rockwell, Clancy Brown, Adam Beach, Paul Dano, Noah Ringer, Keith Caradine./ Audience: MPAA rating: PG-13; for intense sequences of western and sci-fi action and violence, some partial nudity and a brief crude reference.
Keywords: Action and adventure films; Science fiction